فعّاليّة استخدام نموذج التّعليم التّعاوني Inside Outside Circle في تعليم مهارة الكلام لدى طلاّب الفصل السّابع في المدرسة المتوسطة الإسلامية الحكومية 10 أغام - Ayu Ashari; Rita Febrianta (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The reseach in this thesis are to know the effectiveness of using the inside outside circle cooperative learning model in teaching speaking skills to seventh grade students at the 10 Agam State Islamic Middle School. The reseach uses a quantitative with an experimental type. As for number of students in the seventh grade students at the 10 Agam State Islamic Middle School, the researcher used a quantitative with an experimental type. The reseach the sample is in chapter VII.2, as the control chapter, and in chapter VII.3 as the experimental chapter. The researcher uses the experimental design of shih test (Quasi Eksperimen) and analyzes the data using SPSS 26 program. The result of the reseach are: (1) steps for using the  inside outside circle cooperative learning model in teaching speaking skills.(2) there is an effectiveness in using the inside outside circle cooperative learning model in teaching speaking skills to seventh grade students at the 10 Agam State Islamic Middle School and is impact approximately 46 %